Importance of the analytical clinical parameters of severe sepsis in obstructive uropathy (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
INTRODUCTION. Obstructive uropathy (OU) is very prevalent. Its level of bacteremia is high, complicating up to 40% of cases with severe sepsis. OBJECTIVEThe purpose of this clinical case report is to describe medical profiles of patients with Obstructive Uropathy at the HCU of Valladolid.MATERIALS AND METHODSAll patients of legal age urgently admitted with the diagnosis of UO were included. An observational and descriptive prospective study was designed to classify patients into two groups: severe sepsis patients and non-severe sepsis patients.A descriptive and inferential statistical analysis was carried out, considering a p
Keywords: : Obstructive Uropathy, severe sepsis, Urinary diversion